KESADARAN HUKUM PENGELOLAAN SAMPAH OLEH MASYARAKAT SEKITAR DESTINASI WISATA TAPLAU PADANG UNTUK MENCIPTAKAN LINGKUNGAN SEHAT - Yuni Candra; Afriva Khaidir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The realization of community legal awareness in waste management is important to understand and apply extension techniques. Extension techniques are procedures for delivering extension messages to the community who are the target of extension. The techniques used are oral, written and demonstration counseling. The following is the explanation: 1) Oral counseling, the method of delivery in oral language, which consists of direct and indirect oral counseling; 2) Written counseling: Extension media in written language includes making brochures, leaflets, posters / pamphlets; and 3) Counseling on hygiene demonstrations: The media used in the development exhibition in the clean / garbage sector. films, traditional arts groups (ludruk, lenong, calung, puppets, randai and others). In addition to the need for a policy program for legal education and technical guidance for the public in building legal awareness, the government also needs to optimize the improvement of adequate facilities and infrastructure in waste management, especially with the fact that the carrying capacity and capacity of the Final Disposal Site (TPA) has exceeded capacity and the waste recycling processing industry in Padang is not yet available. Even though a waste bank already exists, it is not well organized.